Caracterização de lesões por pressão em pacientes assistidos por um programa domiciliar - Almeida, Diego Bonil de (2016)
Introduction:Home Care (HC)can be defined as a set of possible hospital procedures to be performed at the patient's home. Pressure ulcers (PU) are one of the most common complications at HC .Thus, the target issue of this research was "how are patientswith PU characterized in a HC private service”? To identify the UP prevalence in medical records of a HC private service ; the risk factors and the development of the healing processo these ulcers Methodology: A retrospective, descriptive and exploratory research from the analysis of medical records of patients with pressure ulcers was performed in a domiciliary service of a home healthcare company in the city of São José do Rio Preto between 1998 and 2008 . Qualitative variables were associated by applying the Chi-Square test, and quantitative variables (age and length of staying) were evaluated using Kruskal-Wallis nonparametric test. The Multiple Correspondence Analysis (MCA) was used to assess the relationship between all variables observed, stating as variables, the responseto those which refered to the type of pressure ulcer.Results: The characterization of the subjects showed that from the total 1630 records;183 were selected comprising a total of 238 pressure ulcers. The mean age was 72.8 years. The results of the analysis showed that the prevalence of pressure ulcers in the period was 14.6%, with a predominance of the female population (57.4%). As for location 45.4% of patients had sacral ulcers and 24.8% of these were located in the calcaneus, with a predominance of stage three which represented 55.4% of the sample. The risk factors identified were related to immobility by cerebrovascular accident (CVA) in 29.5%, senile diseases in 19.7% and fractures in 13.7%. Arterial hypertension (AH) was the most frequent former disease in 37.2% and hypertension associated with diabetes mellitus in 12%; standing out the females (57.4%). As topical therapy of wounds, the most used products were Essential Fatty Acids (EFA) in 32.3%, enzyme coverage in 27.7% and hydrogel in 19.7%; from the total PU, 76.5% had been healed.Conclusion: The average rate of pressure ulcers was 14.6%in HC service from 1998 to 2008.Women have comprised most of the population. Sacral locationin stage threewas the most frequent. The most used topical therapy was EFA and most PUs healed. According to the multivariate analysis, sacral ulcer in three and four stages was more frequent in males and, in general, has not healed. The frequency of calcanealulcer was higher in patients over 70 years, with two years of home care and victims of stroke. The trochanteric ulcer in stage one and two was more frequent in women between 60 and 69 years, with some kind of fracture. These ulcers mostlyhealed and patients were discharged fromhome care.